BIOGAS MARKET RESEARCH IN EU COUNTRIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Recently, the development of renewable energy is considered one of the important criteria for energy security in the world. The article examines the potential and possibilities of biogas production in the EU countries due to the available biological waste and agricultural raw materials. The state of technology and development of the biogas market, the dynamics of production and conversion of biogas into electricity are characterized. It is determined that an important reason for the need to increase the use of renewable energy sources is the uncontrolled growth of household and industrial waste, which leads to environmental pollution and requires high costs for disposal. It is studied that modern methods of waste management through the production of biogas and biomethane can not only alleviate the global energy crisis, but also effectively protect the ecology of the environment. It is emphasized that biogas will play a key role in achieving Europe's long-term goals for energy security and mitigating the effects of climate change, as part of a promising and balanced complex of renewable energy sources. It has been proven that the production and use of biogas has a number of justified and confirmed by world practice advantages, since the availability of a wide range of necessary raw materials for the production of biogas and biomethane allows the construction of biogas plants in areas of concentration of agricultural production and technologically related industries. Special attention is paid to the role played by biogas and biomethane in the fight against climate change and the development of sustainable technologies, since sustainable development is the basis of the well-being of EU countries, it is respect for the environment in which the population of European countries lives and their future generations will live. This ideology underlies the development of the biogas industry in Europe. Based on statistical data of past periods and regression analysis, a calculation of the forecast volumes of energy production from biogas and biomethane in EU countries was made using a trend model and Excel spreadsheet editor. Considering the development perspective, it is determined that the transition to sustainable energy remains the most important for the EU economy, where the biogas sector can already provide a competitive and sustainable alternative to imported fossil gas thanks to domestic production.